OWLS, AS REGARDED BY THE SCIENTISTS AND AGRICULTURISTS THROUGHT THE WORLD AND IN PAKISTAN - M. Mahmood-ul-Hassan (Journal of Animal and Plant Sciences, 2006)
Pakistan is an agricultural country where majority of rural population comprise small land holders. A considerable part of their agricultural produce is lost annually to vertebrate pests. Natural control agents viz., the owls have never been used intentionally in the country to minimize the losses inflicted by pest rats and mice. The major impediment in using these birds effectively against vertebrate pests are the old beliefs which associate owls with death and desolation resulting in an over all hatred response of a layman towards owls. The present paper aims to describe the role that owls can play in boosting the economy of the country and to create some respect towards these birds by highlighting their farmer friendly attitude.
Keywords: Agricultural economy; Barn owl; Beliefs; Toes and talons; Vermin